1986
DOI: 10.1113/jphysiol.1986.sp016189
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of vasodilation induced by alpha‐human atrial natriuretic polypeptide in rabbit and guinea‐pig renal arteries.

Abstract: SUMMARY1. Effects of a-human atrial natriuretic polypeptide (a-HANP) on electrical and mechanical properties of smooth muscle cells of the guinea-pig and rabbit renal arteries and of the guinea-pig mesenteric artery were investigated.2. a-HANP (up to 10 nM) modified neither the membrane potential nor resistance of smooth muscle cells of the guinea-pig and rabbit renal arteries. In the guinea-pig mesenteric and renal arteries, a-HANP (up to 10 nm) had no effect on the amplitude and facilitation (mesenteric arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The time course of the peak increases in cyclic GMP coincides with the peak relaxant effect (attained in around 5 min), an observation in agreement with that of Ishii & Murad (1989). The mechanism by which cyclic GMP may induce relaxation remains to be elucidated, however, some reports suggest modulation of transmembrane mobilisation of Ca2", possibly through activation of a calcium extrusion pump (Popescu et al, 1985;Ishihera et al, 1985;Fujii et al, 1986). In summary, this investigation suggests, for the first time, a role for both the elevation of cyclic GMP and the opening of ATP-sensitive and small conductance calcium-activated K+ channels in response to urodilatin.…”
Section: C -)supporting
confidence: 66%
“…The time course of the peak increases in cyclic GMP coincides with the peak relaxant effect (attained in around 5 min), an observation in agreement with that of Ishii & Murad (1989). The mechanism by which cyclic GMP may induce relaxation remains to be elucidated, however, some reports suggest modulation of transmembrane mobilisation of Ca2", possibly through activation of a calcium extrusion pump (Popescu et al, 1985;Ishihera et al, 1985;Fujii et al, 1986). In summary, this investigation suggests, for the first time, a role for both the elevation of cyclic GMP and the opening of ATP-sensitive and small conductance calcium-activated K+ channels in response to urodilatin.…”
Section: C -)supporting
confidence: 66%
“…For example, besides the action observed here, it is reported that the peptides inhibited the release of calcium from intracellular stores of vascular smooth muscles (Fujii et al, 1986;MEISHERI et al, 1986) or stimulated calcium extrusion from the cells (Fujii et al, 1986). The concentration of a-hANP used in the present study was comparable to or lower than that required to produce the above actions.…”
Section: Discussionmentioning
confidence: 53%
“…SATO et al mediate the action in each tissue WINQuIsT et a!., 1984), the cellular or molecular mechanisms of actions of the peptides have not been fully elucidated. As for its vasorelaxing action, some mechanisms are postulated, such as an inhibition of Ca release from intracellular stores (CHID et al, 1986;FuJII et al, 1986;MEISHERI et al, 1986), acceleration of Ca extrusion from cells (FuJII et al, 1986;WINQUIST, 1986), or a blockade of receptor-operated Ca channels (CHID et al, 1986;WINQUIST, 1986). Unlike endogenous digitalis-like substance (HARDY et al, 1979;HAMLYN et al, 1982) which also causes natriuresis possibly through inhibition of the Na, KATPase in a nephron, atrial peptides do not inhibit the enzyme (THIBAULT et al, 1983;PAMNANI et a!.,1984;AALKJAER et a!., 1985).…”
mentioning
confidence: 99%
“…Second, flow-induced NO production was less in SHR than in WKY. Moreover, recent evidence (28)(29)(30)(31)(32)(33) has shown that 8-bromo-cyclic GMP, sodium nitroprusside, and atrial natriuretic peptide attenuate phosphatidylinositol turnover in platelets and vascular tissues, and that cyclic GMP inhibits the interactions between GTP-binding protein and PLC in cultured aortic VSMC. Because NO may suppress PLC activity and because PLC may be one main source of AA release during shear stress, less NO production may result in less inhibition of PLC activity, which would increase prostacyclin formation in SHR but not in WKY.…”
Section: Discussionmentioning
confidence: 99%